A Proposal for Developing the Cost Sharing of Higher Education in Saudi Arabia in Light of Some International Experiences - Mohamed Mohamedy Mokhles (University of Science and Technology, Yemen, 2016)
Abstract: The present study aims to explore the current situation of cost sharing of higher education in the Kingdom of Saudi Arabia , to compare it to the higher education in England and America, and to identify differences and  similarities and differences  between them.  The researcher used George Berday's approach in comparative studies. Results have shown  that there is a shortcoming in the procedures of reducing the cost of governmental higher education in Saudi Arabia and in the methods of funding and procedures of disbursement and allocation of the university., There are also shortcomings in the programs of linking between scientific research and the needs of the labor market  due to  the fact that  the university does not get involved in  major industrial enterprises. There are no partnerships between them in order to make use of scientific research to serve the community and respond to the needs of the labor market. This has led to an increase in the gap between the university outcomes and the needs of the Saudi labor market. On contrary,  both countries, under comparison, take care of all programs that serve the scientific research, community service, and respond to the market needs. However, the Kingdom of Saudi Arabia relies on traditional methods to reduce the cost of Higher education, including, restricted admission for  male and female students, increasing tuition fees, and  requiring rent for facilities, and reducing indirect costs.